2007
DOI: 10.1016/j.cell.2007.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Enhances Learning via Norepinephrine Regulation of AMPA-Receptor Trafficking

Abstract: Emotion enhances our ability to form vivid memories of even trivial events. Norepinephrine (NE), a neuromodulator released during emotional arousal, plays a central role in the emotional regulation of memory. However, the underlying molecular mechanism remains elusive. Toward this aim, we have examined the role of NE in contextual memory formation and in the synaptic delivery of GluR1-containing alpha-amino-3-hydroxy-5-methyl-4-isoxazoleproprionic acid (AMPA)-type glutamate receptors during long-term potentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
469
5
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(505 citation statements)
references
References 74 publications
27
469
5
4
Order By: Relevance
“…However, I-O curve MEP amplitudes were enhanced under both single-dose and chronic RBX conditions. Animal studies showing that noradrenaline enhances glutamatergic facilitation in the hippocampus might explain these results, as higher TMS intensities of the I-O curve are affected by glutamatergic mechanisms (Hu et al, 2007). Moreover, our results are in line with previous human studies that found that single-dose RBX and the presynaptic α2-antagonist yohimbine increase the slope of I-O curve but do not alter MTs (Plewnia et al, 2001(Plewnia et al, , 2002(Plewnia et al, , 2004.…”
Section: Discussionsupporting
confidence: 92%
“…However, I-O curve MEP amplitudes were enhanced under both single-dose and chronic RBX conditions. Animal studies showing that noradrenaline enhances glutamatergic facilitation in the hippocampus might explain these results, as higher TMS intensities of the I-O curve are affected by glutamatergic mechanisms (Hu et al, 2007). Moreover, our results are in line with previous human studies that found that single-dose RBX and the presynaptic α2-antagonist yohimbine increase the slope of I-O curve but do not alter MTs (Plewnia et al, 2001(Plewnia et al, , 2002(Plewnia et al, , 2004.…”
Section: Discussionsupporting
confidence: 92%
“…The hippocampus receives dopaminergic, noradrenergic and cholinergic inputs that can modulate LTP induction and consolidation (Frey et al, 1991;Frey et al, 1990;Gelinas and Nguyen, 2005;Hu et al, 2007), and play a role in synaptic capture of both L-LTD and L-LTP, likely by regulating the induction of PRPs and thereby priming the cells for synaptic capture (Navakkode et al, 2007;Sajikumar and Frey, 2004a). However, ascending monoaminergic fibers may also facilitate hippocampal LTP induction and LTP-dependent learning processes in a global manner during arousal and attention by suppressing the slow afterhyperpolarization (sAHP) and increasing intrinsic excitability…”
Section: Cell-wide Facilitation Modulation Of Intrinsic Excitabilitymentioning
confidence: 99%
“…Neurons in the CA1 area of the hippocampus receive strong neuromodulatory innervation, which has been involved in a range of behavioral processes, from novelty detection to arousal and contextual habituation in the mouse. The participation of dopaminergic input in STC (Sajikumar and Frey, 2004a) may explain why neuromodulatory events with an emotional component, such as stress, pain or pleasure may lead to flashbulb memories (Ahmed et al, 2006;Hu et al, 2007;Sajikumar et al, 2007b;Seidenbecher et al, 1997). In fact, experiments analyzing LTP reinforcement in DG by exploratory behavior has been proposed as a first evidence for STC events during behavioral process (Reymann and Frey, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The function of AMPARs is rapidly modulated by phosphorylation at two sites on the GluR1 subunit, and both sites are implicated in the expression of synaptic plasticity and memory [121] . GluR1 phosphorylation is transiently increased by stress, possibly contributing to the stress-induced facilitation of memory [122] . In addition, the AMPAR potentiators LY392098 and LY451646 have antidepressant effects in the FST and TST [123][124][125] .…”
mentioning
confidence: 99%